PENENTUAN WAKTU BAKU PADA PRODUKSI SABUK JUMBO BAG MENGGUNAKAN METODE TIME STUDY PADA PT. SAMI SURYA PERKASA - Muhammad Fajar Santoso; Ayudyah Eka Apsari, Nancy Otyajati, Sri purwati (PROSEDING, 2022)
A company definitely wants to have maximum profit. Maximum profit can be achieved if a company has optimal standard time. PT Sami Surya Perkasa has not set a standard time for the production of jumbo bag belts so that the production of jumbo bag belts is produced without a planned target. To find out the work target of this jumbo bag belt, the author conducted a study using the time study method. And produce the raw time for making a jumbo bag belt with the work stages of preparing 99.04 materials, processing 16.07 threads, winding the finished belt 12.98, cutting the belt 8.64, sewing the entire jumbo bag belt 4.93. So it is found that the standard time for making jumbo bag belts is 141.66 seconds. Or if changed in minutes to 2.3 minutes. With this standard time, the company can set productivity standards in the manufacture of jumbo bag belts. Keywords: Normal Time, Standart Time, Time Study, Work Measurement